Pengembangan Sistem Informasi Kredit Sahabat Pada Badan Usaha Milik Desa (Bumdes) Moyo Berbasis Android - Delia, Khofifah; Esabella, Shinta (Management of Information System Journal, 2023)
riend Credit at the Moyo Village-Owned Enterprise (BUMDes) serves as a suggestion for borrowing funds for Moyo villagers. The location is located in Moyo Village, Moyo Hilir sub-district, Sumbawa Regency, West Nusa Tenggara. This research aims to develop a Friendly Credit Information System for Village-Owned Enterprises (BUMDes) Moyo by users (community) which aims to produce a more attractive and easily accessible display via an Android smartphone. The results of this study are a friendly credit information system for Moyo village-owned enterprises (1BUMDes) based on android on the user (community) side using the Rappit Application Deploment (RAD) software development method, Unified Modeling Language (UML) modeling, and dart language flutter and using black box testing